FEARING EKSISTENCE OF ARTICLE 135 OF THE INDONESIAN IMMIGRATION LAW RELATED TO PROOFING OF FALSE MARRIAGE AT IMMIGRATION CRIME - Koesmoyo Ponco Aji; Aditya Tri Kurniawan (Jurnal Ilmiah Kajian Keimigrasian, 2018)
Pseudo-marriage or false marriage is one type of crime that is difficult to prove, so that until now there has never been a case of pseudo marriages stated by the prosecutor's office that the enforcement of immigration laws related to pseudo marriages is in Article 135 of Law No. 6 of 2011 concerning immigration has never been done, although there have been many suspected cases of pseudo-marital acts. This is because both Foreign Citizens as Indonesian actors and Citizens who are wives or husbands who are made guarantor after making legal marriages in obtaining immigration documents and / or citizenship of the Republic of Indonesia are protecting each other so that the immigration crime cannot be requested responsibility. The proof of the elements of immigration criminal acts of apparent marriage can be seen from the notion of false marriage itself.